The Effect of Environmental, Social and Governance (ESG) Assessment on Firm Value with Profitability as a Mediating Variable - Devi Cheilsa Sumarno; Wuryan Andayani; Yeney Widya Prihatiningtias (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
The development of recent issues regarding the climate change crisis, the impact of environmental damage, social welfare and good governance has forced several companies to adopt new assessment metrics Therefore, this study aims to analyze and examine the effect of ESG valuation on firm value, which is mediated by profitability. This quantitative research used secondary data, and the test used path analysis. The study's results prove that profitability (ROA) can mediate the relationship between ESG assessment and firm value (Tobin's Q). This study concludes that investors still see the value of profitability in considering the company's value in the future due to making investment decisions. This leads to capitalism, which means that investors still have difficulty exploiting the ESG aspect, so they must be assisted by looking at financial performance improvement in selecting companies for making investment decisions in the capital market.